2000
DOI: 10.1115/1.1285988
|View full text |Cite
|
Sign up to set email alerts
|

Closed-Form Collapse Moment Equations of Elbows Under Combined Internal Pressure and In-Plane Bending Moment

Abstract: Elastic-plastic finite element analysis has been carried out to evaluate collapse moments of six elbows with elbow factors varying from 0.24 to 0.6. The loading conditions of combined in-plane closing/opening bending moment and varying degree of internal pressure are considered in the analysis. For each case, collapse moment is obtained by twice elastic slope method from the moment versus end-rotation curve. Based on these results, two closed-form equations are proposed to evaluate the collapse moments of elbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(40 citation statements)
references
References 6 publications
1
39
0
Order By: Relevance
“…Full-scale pipe test data for circumferential through-wall cracked elbows under in-plane bending were taken from the published works by an Indian research group [13][14][15][16][17][18][19][20]; the pipe test set-up is schematically illustrated in Fig. 13.…”
Section: Summary Of Test Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Full-scale pipe test data for circumferential through-wall cracked elbows under in-plane bending were taken from the published works by an Indian research group [13][14][15][16][17][18][19][20]; the pipe test set-up is schematically illustrated in Fig. 13.…”
Section: Summary Of Test Datamentioning
confidence: 99%
“…On the other hand, despite its common use in power plants, published works on LBB analysis for through-wall cracked elbows are still limited. Most of the existing works on elastic-plastic J and COD estimation methods for elbows have been done by an Indian research group [13][14][15][16][17][18][19][20]. Using extensive elastic-plastic finite element (FE) solutions, they developed an engineering estimation method, similar to the GE/EPRI approach [18,20], to estimate elastic-plastic J and COD for http://dx.doi.org/10.1016/j.engfracmech.2015.06.022 0013-7944/Ó 2015 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…MultiPoint-Constraint (MPC) node was placed at the centre of the end plane of the attached straight pipe where end surface nodes were connected to MPC nodes. One end of the straight pipe was fixed and rotation boundary condition was applied at the other end for inplane opening bending moment, as the analysis is rotation controlled [25].…”
Section: Fe Modeling and Mesh Refinementmentioning
confidence: 99%
“…As pipe bends are flexible components, the large geometry change effect could be important, and accordingly its effect on plastic behaviour of pipe bends has been also investigated extensively (Chattopadhyay et al 2000(Chattopadhyay et al , 2004bKim and Oh 2006b). It was found that, due to change in the cross-sectional shape, the bending direction significantly affects plastic behaviour of pipe bends.…”
mentioning
confidence: 99%
“…Earlier limit load solutions for pipe bends were based either on empirical ones using experimental data (Greenstreet 1978;Griffiths 1979) or on analytical ones (Spence and Findlay 1973;Calladine 1974;Goodall 1978), as summarized in Miller (1986Miller ( , 1988). More recently, although some experimental works have been done (Yahiaoui et al 2002;Chattopahyay et al 2004a), numerical analyses using finite element (FE) methods are increasingly popular Younan 1998, 1999;Chattopadhyay et al 2000Chattopadhyay et al , 2004bRobertson et al 2005;Yahiaoui et al 2000;Oh 2006a, b, 2007). For 90 • pipe bends under combined pressure and in-plane bending, Kim and Oh (2006a) performed extensive geometrically linear FE analyses using elastic-perfectly plastic materials, and found that published analytical solutions (Spence and Findlay 1973;Calladine 1974;Goodall 1978) were much lower than FE results.…”
mentioning
confidence: 99%